BIODIESEL AND URBAN TRANSPORT: A VIEW ON ACADEMIC RESEARCH ON THE WEB OF SCIENCE OVER THE LAST TEN YEARS (Revista Brasileira de Contabilidade e Gestão, 2021)
The emission of carbon dioxide from urban transport is a problem both in Brazil and in other parts of the world and this requires thinking about ways to mitigate its negative impacts. More sustainable fuel, Biodiesel, and relate it to the focus of the problem, which is urban transport. The bibliometric method was used, aiming to expand the knowledge regarding international publications related to the Biodiesel topic in the Web of Science database from 2010 to 2019. The results show that publications in the area have gradually increased over time and that most of the research was published in the journal Energy Fuels.
Keywords: Biodiesel; Sustainable Development; Web of Science